Exercise-Based Pulmonary Rehabilitation for Interstitial Lung Diseases: A Review of Components, Prescription, Efficacy, and Safety - Renata G. Mendes; Viviane Castello-Simões; Renata Trimer; Adriana S. Garcia-Araújo; Andrea Lucia Gonçalves Da Silva; Snehil Dixit; Valéria Amorim Pires Di Lorenzo; Bruno Archiza; Audrey Borghi-Silva (Frontiers Media S.A., 2021)
Interstitial lung diseases (ILDs) comprise a heterogeneous group of disorders (such as idiopathic pulmonary fibrosis, sarcoidosis, asbestosis, and pneumonitis) characterized by lung parenchymal impairment, inflammation, and fibrosis. The shortness of breath (i.e., dyspnea) is a hallmark and disabling symptom of ILDs. Patients with ILDs may also exhibit skeletal muscle dysfunction, oxygen desaturation, abnormal respiratory patterns, pulmonary hypertension, and decreased cardiac function, contributing to exercise intolerance and limitation of day-to-day activities. Pulmonary rehabilitation (PR) including physical exercise is an evidence-based approach to benefit functional capacity, dyspnea, and quality of life in ILD patients. However, despite recent advances and similarities with other lung diseases, the field of PR for patients with ILD requires further evidence. This mini-review aims to explore the exercise-based PR delivered around the world and evidence supporting prescription modes, considering type, intensity, and frequency components, as well as efficacy and safety of exercise training in ILDs. This review will be able to strengthen the rationale for exercise training recommendations as a core component of the PR for ILD patients.